INFORMATION SECURITY AS A SYSTEM OF PUBLIC RELATIONS AND OBJECT OF LEGAL PROTECTION - Kaletnik, Vasyl (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2022)
Purpose: analysis of modern views on understanding the content and essence of the concept of «information security» as a system of social relations and an object of legal protection. Methods: in the study, the author used methods of theoretical analysis and content analysis, monographic method, method of systematization to identify and specify the author’s position within the studied issues. When preparing conclusions and recommendations based on the results of the study, the method of generalization was used. Results: the author considered different views on the understanding of the content and essence of the concept of «information security» in the context of two main approaches - technological (as the main criteria singles out the provision of confidentiality, integrity and availability of information) and humanitarian (focuses on protection against information threats). According to the results of the review, it is emphasized that information security is a complex constitutional and legal construction, which is determined by: complex social and legal nature, based on the diversity of information relations in society; differentiation of subjects of information relations, which have their own interests, rights and obligations in this area; the objective nature of information relations, which determine the development of world civilization and the system of international law. Discussion: the multiplicity of definitions of the concept of «information security» presented in various normative legal acts prevents the correct application of legislative provisions and indicates the need for the formation of a legislative thesaurus of definitions in the field of information law.